Resistance in everyday life and the performativity of the Turkish minority in Bulgaria (1946–1989) - Ciddi, Onur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis examines the passive and mild resistance developed by the Muslim Turkish minority, who lived in Bulgaria during the period of the People's Republic of Bulgaria, against assimilation policies, on the basis of personal identity, culture, and everyday life habits. The study focuses on the period between 1946 and 1989, an era which has been relatively neglected in terms of history writing. In this context, while revealing the long-term assimilation policy against the Muslim Turkish minority, it also sheds light on a special period in the history of the People's Republic of Bulgaria. The study ethnographically covers the villages of Buranlar, Kufallar, and Omranköy in Bulgaria. It examines the daily life practices and performances developed against the assimilation policies of the state as a kind of "passive resistance", through the recollections of the social and cultural experiences of those who still live in these villages and others who migrated to Turkey. This study also reveals that, contrary to what has been put forward so far, the long-term assimilation policy in Bulgaria towards the Turkish Muslim minority began to form from the early years of the founding of the People's Republic of Bulgaria. In this context, this work is carried out to bring a new perspective to minority studies in Bulgaria.
Keywords: Turks -- Bulgaria.; Muslims -- Cultural assimilation -- bBulgaria.; Minorities -- Cultural assimilation -- bBulgaria.